2009
DOI: 10.1080/00016480802579058
|View full text |Cite
|
Sign up to set email alerts
|

Sulcus configurations of vocal folds during phonation

Abstract: Thirty-two patients (21.9%) were type I, 61 (41.8%) were type II, and 53 (36.3%) were type III. Different sulcus configuration groups had significantly different roughness and mean fundamental frequency. Type III was significantly different from type I and type II in grade, breathiness, mean flow rate, subglottic pressure, maximum phonation time, Jitter%, and harmonics to noise ratio. The pathologic sulcus showed distinctive features in electroglottograph waveform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
1
12
1
4
Order By: Relevance
“…Only one individual displayed mild breathlessness ( Table 2 ). This result contradicts literature findings, 5 6 7 10 11 12 in which breathlessness is the primary auditory perception alteration in patients with sulcus vocalis. Hirano et al (1990) 11 assessed 126 patients with sulcus vocalis and most of the individuals exhibited mild breathlessness and hoarseness.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Only one individual displayed mild breathlessness ( Table 2 ). This result contradicts literature findings, 5 6 7 10 11 12 in which breathlessness is the primary auditory perception alteration in patients with sulcus vocalis. Hirano et al (1990) 11 assessed 126 patients with sulcus vocalis and most of the individuals exhibited mild breathlessness and hoarseness.…”
Section: Discussioncontrasting
confidence: 95%
“…The real incidence of sulcus vocalis is unknown, due to three factors: lack of knowledge of this laryngeal alteration, diagnostic error, or the absence of diagnosis when vocal symptoms are not serious enough to cause vocal complaints. 6 Currently, examinations such as videolaryngoscopy, videolaryngostroboscopy or suspension microlaryngoscopy are used to investigate morphological and structural changes in the vocal cords, although it is important to consider the data related to the clinical history of vocal alterations. 1 6 7 8 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deterioration of voice in sulcus cases varies markedly, but the majority of patients had a mild-to-moderate grade of hoarseness, roughness, breathiness, or strained voice [ 38 , 39 ]. Our results, as with other studies [ 11 , 23 , 25 , 37 ], showed a significant improvement of GRBAS scale parameters, although the patients’ voices remained hoarse after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of glottal closure was rated on a 6-point scale according to Lim’s proposal 22 as follows: 0, complete closure; 1, anterior glottic chink; 2, posterior chink; 3, spindle glottic chink; 4, irregular glottic chink; 5, incomplete glottic closure (no glottal contact).…”
Section: Methodsmentioning
confidence: 99%